Sustainable management using recycle and reuse of construction waste materials in Malaysia / Shaharin Hamid ... [et al.] - Hamid, Shaharin; Mat Isa, Che Maznah; N. Felix, Shamer; Mustaffa, Nur Kamaliah (Universiti Teknologi MARA Cawangan Pulau Pinang, 2020)
Ineffective construction waste management has become a serious problem that impacted significantly to environmental pollutions especially in a developing country like Malaysia. Despite the enactment of law by the government, Malaysia is still far behind as compared to other countries like Denmark and Hong Kong in terms of implementation of recycling and reuse of construction waste. Recycling and reuse of waste materials seems to be a profitable method that will boost the lifetime of landfills and cut down the usage of virgin natural resources. This paper discusses the practices of recycling and reuse of construction waste materials in the Klang Valley. A questionnaire survey was administered to 117 respondents from construction companies. The most common types of construction waste materials that can be recycled and reused are concrete, metal, asphalt, brick, plastic, cardboard, timber and glass. A descriptive analysis using Relative Important Index (RII) was used to rank the items asked in the survey. It was found that the most frequent types of recycling and reuse of construction waste materials based on ranking is timber, while the key benefit of recycle and reuse of construction waste is reduction of landfill space. On the other hand, the key challenge that affects recycling and reuse of construction waste is the risk of contamination. This study is beneficial for all parties involved in construction activities to achieve a more sustainable construction in Malaysia and throughout the world.